Household reporting of childhood respiratory health and air pollution in rural Alaska Native communities - Ware, Desirae N. (Co-Action Publishing, 2014)
BACKGROUND: Air pollution is an important contributor to respiratory disease in children. OBJECTIVE: To examine associations between household reporting of childhood respiratory conditions and household characteristics related to air pollution in Alaska Native communities. DESIGN: In-home surveys were administered in 2 rural regions of Alaska. The 12-month prevalence of respiratory conditions was summarized by region and age. Odds ratios (ORs) were calculated to describe associations between respiratory health and household and air quality characteristics. RESULTS: Household-reported respiratory health data were collected for 561 children in 328 households. In 1 region, 33.6% of children aged <5 years had a recent history of pneumonia and/or bronchitis. Children with these conditions were 2 times more likely to live in a wood-heated home, but these findings were imprecise. Resident concern with mould was associated with elevated prevalence of respiratory infections in children (ORs 1.6–2.5), while reported wheezing was associated with 1 or more smokers living in the household. Reported asthma in 1 region (7.6%) was lower than national prevalence estimates. CONCLUSIONS: Findings suggest that there may be preventable exposures, including wood smoke and mould that affect childhood respiratory disease in these rural areas. Additional research is needed to quantify particulate matter 2.5 microns in aerodynamic diameter or less and mould exposures in these communities, and to objectively evaluate childhood respiratory health.